2014
DOI: 10.1002/pssa.201330252
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure, electrical properties, and electric field‐induced phase transitions in NaNbO3–LiTaO3 lead‐free ceramics

Abstract: Lead-free ceramics (1-x)NaNbO 3 -xLiTaO 3 were synthesized by an ordinary solid-state reaction method. Rietveld analysis reveals that the crystal structure changes from one orthorhombic phase with Pbcm space group to another orthorhombic phase with P222 1 space group when increasing x. The morphotropic phase boundary between two different orthorhombic symmetries is formed at 0.14 < x < 0.18. Excess LiTaO 3 causes an abnormal grain growth behavior. The pure NaNbO 3 presents four current peaks in the I-E loop, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…The obtained value of P r ≈ 8.5 μC cm −2 is sufficiently lower than the best values of P r ≈ 25–30 μC cm −2 reported for NaNbO 3 ceramics . However, there are many works where much smaller P r values ≈3–8 μC cm −2 were obtained for NaNbO 3 ceramics by studying either P ( E ) loops or by integrating the TSC curve . This large scatter in the P r values may be due to the different quality and grain size distribution of ceramics and the difference in their defect structure.…”
Section: Resultsmentioning
confidence: 59%
“…The obtained value of P r ≈ 8.5 μC cm −2 is sufficiently lower than the best values of P r ≈ 25–30 μC cm −2 reported for NaNbO 3 ceramics . However, there are many works where much smaller P r values ≈3–8 μC cm −2 were obtained for NaNbO 3 ceramics by studying either P ( E ) loops or by integrating the TSC curve . This large scatter in the P r values may be due to the different quality and grain size distribution of ceramics and the difference in their defect structure.…”
Section: Resultsmentioning
confidence: 59%
“…In general, copper oxide, or CuO, compounds are commonly used to enhance the Q m value in piezoelectric ceramics [11][12][13]. However, it should be noted that the 0.88NaNbO 3 -0.12LiTaO 3 composition ceramic without any acceptor doping possesses a high Q m value of 1333 according to our previous study [14].…”
Section: Introductionmentioning
confidence: 89%
“…In our previous work [14], we reported that 12 mol% LiTaO 3doped NaNbO 3 ceramics (0.88NN-0.12LT) sintered at 1310 °C possessed a high Q m , good temperature stability, and a high T C . In this study, we also prepared the samples by an ordinary ceramic technique using metal oxides and carbonate powders: Na 2 CO 3 (99.8%), Li 2 CO 3 (98%), Nb 2 O 5 (99.99%), and Ta 2 O 5 (99.99%).…”
Section: Materials Synthesismentioning
confidence: 97%
“…NaNbO 3 ceramics exhibit a ferroelectric phase with electric field and possess piezoelectric properties ( d 33 ∼ 20 pC/N). However, the antiferroelectric phase is prevalent at room temperature. To realize the stable existence of the ferroelectric phase in NN-based ceramics, researchers introduced LiTaO 3 , BaTiO 3 , ,, and (K 0.5 Bi 0.5 )­TiO 3 , as the second component to obtain NN-based piezoelectric ceramics with a stable ferroelectric phase. Zeng et al.…”
Section: Introductionmentioning
confidence: 99%